2009
DOI: 10.1159/000228892
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish as a Genetic Model in Biological and Behavioral Gerontology: Where Development Meets Aging in Vertebrates – A Mini-Review

Abstract: Understanding the molecular mechanisms of aging in vertebrates is a major challenge of modern biology and biomedical science. This is due, in part, to the complexity of the aging process and its multifactorial nature, the paucity of animal models that lend themselves to unbiased high-throughput screening for aging phenotypes, and the difficulty of predicting such phenotypes at an early age. We suggest that the zebrafish genetic model offers a unique opportunity to fill in this gap and contributes to advances i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 142 publications
3
65
0
Order By: Relevance
“…Cnc and Skn-1 have been reported to play a critical role in the regulation of life span in flies and worms, respectively (2,43), but the roles of Nrf2 in vertebrate longevity have not been sufficiently investigated (36). Recent studies have shown that the zebrafish is a potentially valuable model for aging research (12,24). The relationship between longevity and Nrf2 functions can be analyzed using the nrf2 fh318 mutants examined in this study.…”
Section: Fig 2 Survival Rate Of Nrf2mentioning
confidence: 98%
“…Cnc and Skn-1 have been reported to play a critical role in the regulation of life span in flies and worms, respectively (2,43), but the roles of Nrf2 in vertebrate longevity have not been sufficiently investigated (36). Recent studies have shown that the zebrafish is a potentially valuable model for aging research (12,24). The relationship between longevity and Nrf2 functions can be analyzed using the nrf2 fh318 mutants examined in this study.…”
Section: Fig 2 Survival Rate Of Nrf2mentioning
confidence: 98%
“…The recent and remarkable discovery that birds and reptiles lack the DAT transporter (Lovell et al, 2015) reduces the choice of vertebrate models to mammals and fish. Among those, the diurnal vertebrate zebrafish model offers multiple advantages, including its well-developed DA system (Panula et al, 2010), gradual aging (Kishi et al, 2009) and sensitivity to multiple drugs of abuse and their withdrawal (Bencan et al, 2009; López Patiño et al, 2008a; Riley et al, 2015; Rinkwitz et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Likewise, transgenic mouse studies show that neurodegeneration itself may contribute to obesity [253]. Given the utility of zebrafish models to study aging [254,255], obesity (Tables 2 and 3) and neurodegeneration [256,257], it is possible to expect that novel aquatic models can be useful to mimic pathogenetic interplay between metabolic and neurodegenerative disorders. With the growing population affected by obesity, AD and PD worldwide [258], this direction of zebrafish biomedical research becomes especially timely and clinically relevant.…”
Section: Future Direction Of Researchmentioning
confidence: 99%